The process of linguistic communicating at Roman Jacobson - Zian, Laila (Arab Journal for Sciences and Research Publishing, 2016)
Lingual lesson has significant development at the level of modern approaches to the study of language, And this development has generated various interpretations on the level of language function; Either linguistically or socially exclusive, resulting in differences in the interpretation of linguistic phenomenon in itself, As well as the serious procedural tools that help us interpret the text or speech which language, newest vehicles,  Jacobsen is a scientific contribution theory appears in the context of the analysis of the linguistic phenomenon.And the theory of linguistic communication is one of the most important modern theories of linguistics, and Roman Jacobson is a true parallax them; as it is attributed to him at all despite The first signs appeared to Saussure where this theory has shown that the language is based on the basic functions in the process communicative identified six elements: the sender: the expressive function, and the receiver: the evocative function, and the message and function of poetry, and the channel: the phatic function, and the context: referential function, the code: the metalingual functions.Jacobson interested in linguistic communication and nonlinguistic communication, and given the importance of the context; where to put its mark in many areas of knowledge; including pedagogy, sociology, media, science and communication, among others.
Keywords: linguistics; language; communication; job; discourse